Bank regulatory size thresholds, merger and acquisition behavior, and small business lending - Bindal, Shradha; Bouwman, Christa H.S.; Hu, Shuting (Sophia); Johnson, Shane A. (Journal of Corporate Finance, 2020)
Size threshold-based regulatory requirements are pervasive in banking, but little is known about how they affect the merger and acquisition (M&A) behavior of banks around the thresholds. M&As cause discrete increases in size, so we hypothesize changes in banks' M&A behavior near regulatory size thresholds and associated real effects (changes in small business lending by the acquiring banks). We develop a novel research design that estimates indirect treatment effects for banks just below the thresholds. We find strong evidence of indirect treatment effects on bank M&A behavior and the small business lending of the merged banks. Our results illustrate the importance of indirect treatment effects in difference-in-differences studies involving size thresholds.